Discourse Analysis of Komeng's Humor In The Political Episode Uhuy Komeng Secrets Of Escaping To Senayan In YouTube Channel Rosi Kompas TV - Fatma Zairawati; Wahyudi Rahmat; Refa Lina Tiawati (Jurnal Bebasan, 2024)
The primary objective of this study is to identify the types of humor employed and to examine humor discourse both textually and contextually. This research uses a qualitative approach. Data collection involved in-depth techniques, such as unobtrusive observation and note-taking. The analyzed data consists of a video episode titled  Politics Uhuy: Komeng’s Secret to Getting to Senayan,” uploaded by the Rosi Kompas TV YouTube Channel on February 22, 2024. The video, lasting 1 hour and 3 minutes, had  pproximately 3 million views. For data analysis, the study applies Astuti's framework on forms of humor discourse alongside Wijana and Rohmadi's theories on humor  ontext. The results reveal multiple forms of humor in the episode, including educational, political, household, family, ethnic, and religious humor. Notably, no sexual or  romantic humor was observed. The qualitative discourse analysis explores how humor conveys criticism, reflects social realities, and engages with the audience. Findings indicate a predominance of political humor, suggesting that humor is a critical tool for discussing political issues. Also, humor connects with the audience by referencing cultural elements and social values. Contextual analysis reveals that humor functions as entertainment and an effective medium for delivering social and political messages.